2005
DOI: 10.1128/jvi.79.17.10839-10851.2005
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanins in Viral Infections: a Fundamental Role in Viral Biology?

Abstract: 4The tetraspanins are a broadly expressed superfamily of transmembrane glycoproteins with over 30 members found in humans and with homologues conserved through distantly related species, including insects, sponges, and fungi. Members of this family appear to form large integrated signaling complexes or tetraspanin-enriched microdomains (TEMs) by their association with a variety of transmembrane and intracellular signaling/cytoskeletal proteins (49). These interactions link tetraspanins to an array of physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 166 publications
(137 reference statements)
2
91
0
1
Order By: Relevance
“…CD81 À / À mice are hypofertile and CD9 À / À ::CD81 À / À mice are completely infertile, suggesting a cooperative role of CD9 and CD81 in sperm/egg fusion 13 . However, both CD9 and CD81 negatively regulate HIV-induced cell fusion 14 and macrophage fusion 15 . Altogether, these studies indicate that CD9 and CD81 can act both as positive and negative regulators of cell-cell fusion processes.…”
mentioning
confidence: 99%
“…CD81 À / À mice are hypofertile and CD9 À / À ::CD81 À / À mice are completely infertile, suggesting a cooperative role of CD9 and CD81 in sperm/egg fusion 13 . However, both CD9 and CD81 negatively regulate HIV-induced cell fusion 14 and macrophage fusion 15 . Altogether, these studies indicate that CD9 and CD81 can act both as positive and negative regulators of cell-cell fusion processes.…”
mentioning
confidence: 99%
“…There is increasing evidence for the involvement of tetraspanins in infections by various microbes (especially by virus) [13]. Also, it has been reported that CD9 is up-regulated upon T cell activation [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in mammals, the tetraspanins have been known to have roles in the pathology of infectious diseases such as diphtheria, malaria and numerous viral infections (reviewed in Ref. [13]). In this study, a CD9 homologue in a reptile, Chinese soft-shelled turtle, has been cloned and identified for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…GM3, sphingomyelin and cholesterol) and stimulate membrane fusion [51,111] as well as surface proteins that have likewise been linked to membrane fusion in cell-cell and viruscell interactions (e.g. CD9, CD81) [112,113] and finally (5) EVs seem to possess intrinsic cell and tissue targeting properties [114].…”
Section: Harnessing the Intrinsic Biological Effect Of Evsmentioning
confidence: 99%